The effect of storage and different cooking methods on the nutritional quality of chicken breast - Shukri, Suzyelawati Mohd (Universiti Sains Malaysia, 2013)
Chickens are the most popular poultry consumed than others and its nutritional quality of chicken breast is affected by frozen storage and different cooking methods such as boiling, grilling, deep-frying and roasting. A study was conducted to determine the nutritional values in fresh and 7 days of storage of chicken breast meat as affected by different type of cooking. Proximate analysis was carried out following the procedures of AO AC (1996). The results show that storage chicken meat prepared by deep-frying methods had significantly (P 0.05) lowest moisture content (58.46%) compared to other type of cooking. The fat content (12.73%) in fresh chicken meat by deep-frying method was significantly highest (P 0.05) while the highest protein content was found in chicken meat by boiling method (14.26%). Fresh chicken breast meat prepared by deep-frying method had significantly (P 0.05) highest calorie content (5.68kcal/g) compared with boiling (5.46 kcal/g), roasting (5.39 kcal/g) and grilling (5.41 kcal/g). In conclusion, chicken breast varied in proximate and calorie content, which in turn is affected to varying degrees by cooking methods and frozen storage.